THE IMPORTANCE OF MORPHOFUNCTIONAL INDICATORS OF THE LIVER WITH DISSEMINATED ECHINOCOCCOSIS OF THE LIVER AND ABDOMINAL ORGANS - Otakuziev; Otakuziev, A.Z; Nishonov, F.M (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
to improve the morphological and functional state of the liver in patients with disseminated echinococcosis after surgical treatment. Material and methods: analyzed the results of treatment of 58 patients with disseminated echinococcosis of the liver and abdominal organs, operated in the clinic of the Andijan State Medical Institute. Results: detoxification, antioxidant, hepatoprotective agents in combination with other drugs and decompressive interventions are the leading links in the complex treatment of these patients. The unsatisfactory results in the patients of the comparison group confirmed the opinion of the researchers that when infected and moreover, intraorganic dissemination of echinococcosis, contamination of microorganisms is supported by secondary infection of the biliary tree, which dictates the need for a more effective method of antibiotic prophylaxis. Conclusions: the developed complex of measures in patients with disseminated liver echinococcosis before, during the operation and in the postoperative period allowed reducing the number of unsatisfactory results.